Prognostic value of pre-operative atrial fibrillation in patients with heart failure and secondary mitral regurgitation undergoing percutaneous mitral valve repair with MitraClip. (25th November 2020) - Sisinni, A; Godino, C; Pivato, C.A; Adamo, M; Taramasso, M; Scotti, A; Munafo, A; Sala, A; Curello, S; Agricola, E; Colombo, A; Alfieri, O; et al.
Abstract: Background: Limited data are available regarding the independent prognostic role of atrial fibrillation (AF) after transcatheter mitral valve repair with MitraClip. Aims: We sought to evaluate the real impact of pre-operative AF in a wide series of patients with heart failure (HF) and secondary mitral regurgitation (MR) after MitraClip treatment. Methods: The study included 605 patients with severe secondary MR from a multicenter international registry. Patients were stratified into two groups according to the presence or absence of pre-operative AF. The overall prevalence of pre-operative AF was 44%. Primary endpoint was 5-year overall death, secondary endpoints were 5–year cardiac death and first re-hospitalization for acute HF. Results: At 5-year Kaplan-Meier (KM) analysis conducted in the entire study cohort, compared to patients without AF those with AF had significantly more adverse events in term of overall death (67% vs. 43%; p<0.001) (KM curve A) and cardiac death (65% vs. 37%; p=0.001) (KM curve B) and, moderately more re-hospitalization for acute HF (64% vs. 50%; p=0.048) (KM curve C). To account for baseline differences, patients were propensity score matched 1:1. After matching, 342 adequately matched patients were identified: compared to patients without AF, those with AF had higher rates of death and cardiac mortality but similar rates of re-hospitalization for acute HF. Conclusion: In this large 5-year analysis of patients with HF undergoing MitraClip treatment for severe secondary MR, AF is common and associated with higher rates of both overall- and cardiac-death. However, AF doesn't seem to affect the benefit of the procedure in term of re-hospitalization for HF. Funding Acknowledgement: Type of funding source: None